Analisis Faktor yang Berhubungan dengan Kejadian Stres pada Mahasiswa Tingkat Akhir Universitas Islam Negeri Syarif Hidayatullah Jakarta - Nabila Tazkhia S; Wahyudin Rajab; Novia Nuraini (CV. ITTC INDONESIA, 2026)
Background: Stress among final-year students may arise when thesis completion, graduation requirements, and post-study transition demands are perceived to exceed available personal resources. Social Media and support from the surrounding environment may be associated with how students respond to these pressures. Objective: To analyze factors associated with stress among final-year students of the Informatics Engineering Study Program at Syarif Hidayatullah State Islamic University Jakarta in 2026. Methods: This quantitative analytical study used a cross-sectional design. A total of 120 respondents were selected through purposive sampling from a population of 150 students completing their final projects. Stress was measured using 11 stress items from the Depression Anxiety Stress Scale. Social Media, Family Support, Lecturer Support, Peer Support, and Academic Support were assessed using structured questionnaires. Data were analyzed using the Chi-Square test at a 95% confidence level. Results: Seventy-six respondents, or 63.3%, experienced stress. Stress was associated with Social-Media (p<0.001, OR=21.495, 95% CI: 8.021-57.603), Family Support (p<0.001, OR=8.535, 95% CI: 3.550-20.520), Lecturer Support (p<0.001, OR=14.238, 95% CI: 5.330-38.038), Peer Support (p=0.007, OR=2.868, 95% CI: 1.320-6.235), and Academic Support (p<0.001, OR=5.769, 95% CI: 2.514-13.241). Conclusion: All examined factors were significantly associated with stress among final-year students.